Protein D, an immunoglobulin D-binding protein of Haemophilus influenzae: cloning, nucleotide sequence, and expression in Escherichia coli - Janson, Håkan; Hedén, Lars-Olof; Grubb, Anders ; 0000-0002-0125-3662; Ruan, Maorong; Forsgren, Arne (Infection and Immunity, 1991)
The gene for protein D, a membrane-associated protein with specific affinity for human immunoglobulin D, was cloned from a nontypeable strain of Haemophilus influenzae. The gene was expressed in Escherichia coli from an endogenous promoter, and the gene product has an apparent molecular weight equal to that of H. influenzae protein D (42,000). The complete nucleotide sequence of the gene for protein D was determined, and the deduced amino acid sequence of 364 residues includes a putative signal sequence of 18 amino acids containing a consensus sequence, Leu-Ala-Gly-Cys, for bacterial lipoproteins. The sequence of protein D shows no similarity to those of other immunoglobulin-binding proteins. Protein D is the first example of immunoglobulin receptors from gram-negative bacteria that has been cloned and sequenced.